The effect of land use and land cover on climate: comparison between two weather stations - Fritzsons, Elenice (2023)
This work demonstrates the differences between two meteorological stations 16 km away from each other, located in the same metropolitan region and in a similar geographical situation, but with different environments in relation to land use and land cover: one in an urbanized area (Curitiba, PR), another in the suburban area (Colombo, PR). The daily figures of a 6 years window from the National Institute of Meteorology (INMET) were studied using ANOVA for data comparison. Despite the small distance between the stations, the similar altitude, and the absence of important geographic aspects between them, there was a difference in the average temperature of 0.8ºC, which is accentuated in winter and in the month of July, where this difference reaches 1.4ºC for the average of the minimums and 1.5ºC for the dew point. In addition to the temperature being lower at the Colombo station, the relative humidity is almost 20% higher. This difference can be explained by the presence of vegetation (83%) and a small urbanized area (17%) in the suburban area of Colombo, compared to Curitiba with a more predominant urbanized area (97%) and small vegetal cover (3%). This type of study may subsidy the planning of urban and rural environments, especially for large cities or urban conglomerates.